Effects of probiotics, prebiotics, synbiotics and postbiotics on pediatric asthma: a systematic review - Fan, Die; Hu, Jilei; Lin, Ning (Frontiers in Nutrition, 2025)
BackgroundPediatric asthma, a prevalent chronic disease with rising global incidence, imposing substantial healthcare and socioeconomic burdens. Emerging evidence highlights the gut-lung axis as a pivotal therapeutic target, with microbiota dysbiosis implicated in immune dysregulation and airway hyperresponsiveness. This systematic review evaluated the efficacy and safety of probiotics, prebiotics, synbiotics, and postbiotics in pediatric asthma management.MethodsA comprehensive search of PubMed, Cochrane library, Web of Science, and Embase was conducted up to 2nd January 2025. Inclusion criteria encompassed randomized controlled trials (RCTs) evaluating the therapeutic use of probiotics, prebiotics, synbiotics, or postbiotics in children and/or adolescents (<18 years) with asthma.ResultsEighteen studies (13 RCTs, n = 2,419 participants) were analyzed, focusing on children aged < 18 years. Probiotic interventions, predominantly Lactobacillus (5 studies) and Bifidobacterium (5 studies), demonstrated significant reductions in asthma exacerbations and improved pulmonary function, with strain-specific effects linked to Th2 cytokine suppression and gut-lung axis modulation. Postbiotics, including bacterial lysates (OM-85 BV, PMBL®), attenuated airway hyperresponsiveness and systemic inflammation. Synbiotics reduced viral respiratory infections and healthcare utilization. However, there is still a lack of direct RCTs to explore the therapeutic effects of prebiotics on pediatric asthma. Key limitations include methodological heterogeneity (dosing: 108–1010 CFU/day; duration: 8 weeks−12 months) and risk of bias (3 low-risk, 12 with concerns).ConclusionOur findings underscored the potential of microbiota-targeted therapies but highlight the need for standardized protocols, strain-specific trials, and pediatric prebiotic research. Future studies should integrate multi-omics to elucidate mechanisms and optimize personalized interventions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025641318, identifier: CRD42025641318.